Preparation and characterization of magnesium ion gel polymer electrolytes for application in electrical double layer capacitors - Asmara, S.N.; Kufian, M.Z.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2011)
This work describes the preparation and characterization of poly (methyl methacrylate) (PMMA) based gel polymer electrolytes with magnesium triflate (Mg(CF(3)SO(3))(2)) as the ion providing salt. Liquid electrolytes containing 0.4 M Mg(CF(3)SO(3))(2) in solvents comprising different ratios of ethylene carbonate (EC) and diethyl carbonate (DEC) have been prepared at room temperature. The highest conducting electrolyte contains EC and DEC in the weight ratio of 2:1. To the highest conducting liquid electrolyte, 25-50 wt.% PMMA has been added and the mixtures were heated at 80 degrees C for 2 min to form gel polymer electrolytes. The gel electrolyte with composition 40 wt.% PMMA and 60 wt.% of 0.4 M Mg(CF(3)SO(3))(2) in EC:DEC (2:1, w/w) has the highest conductivity of 5.58 x 10(-5)S cm(-1) and activation energy 0.11 eV. The gel polymer electrolyte with highest conductivity at room temperature has Mg(2+) ion transference number of 0.37 and electrochemical stability window 2.42 V. The highest conducting gel polymer electrolyte has been used to fabricate an electric double layer capacitor (EDLC) which exhibits a nearly rectangular voltammogram even after the 50th discharge cycle. The capacitance of the EDLC is about 27 Fg(-1) after the 1st cycle and 23 Fg(-1) after the 50th cycles. (C) 2011 Elsevier Ltd. All rights reserved.